Effectiveness of the eccentric exercise therapy in physically active adults with symptomatic shoulder impingement or lateral epicondylar tendinopathy: A systematic review - Ortega-Castillo, Miguel; Medina-Porqueres, Iván (Elsevier, 2016)
Objectives: To identify and criticize the evidence for the effectiveness of the eccentric exercise to treat upper limb tendinopathies. Design: Systematic review. Methods: Relevant randomized controlled trials (RCTs) were sourced using MEDLINE, SPORT Discus, Physiotherapy Evidence Database (PEDro) and CINAHL databases. Inclusion criteria were: (1) studies in English or Spanish; (2) adult participants with clinical diagnosis of tendinopathy; (3) RCT study design; (4) results regarding pain or strength were assessed; and (5) eccentric exercise was employed to treat upper extremity tendinopathies. Two blinded reviewers independently extracted data concerning trial methods, quality and outcomes. PEDro scale was employed to assess methodological quality. Results were summarized in a best evidence synthesis. Results: The selected studies (n=12) scored an average of 6/10 based on the PEDro score. In 11 studies, pain decreased significantly with eccentric exercise, but only in five studies, the reduction was significantly better than in the non-eccentric group (in all or some of the parameters). Strength was assessed in nine studies; within-group evaluations show that strength significantly improved in the eccentric-group in seven studies, whereas inter-group changes were only significantly better in the eccentric-group in three studies for all the parameters and in two studies for some of the parameters. Conclusions: Eccentric exercise may reduce pain and improve strength in upper limb tendinopathies, but whether its effectiveness is much better than other forms of treatment remains questionable. Further investigations are needed, not only focused on shoulder impingement or epicondylar tendinopathy, but on tendinopathies in other areas of the upper limb.
Keywords: Tendones; Tendon; Overuse injury; Eccentric exercise; Systematic review